KONTRIBUSI KEKUATAN OTOT LENGAN, KELENTUKAN PINGGANG, DAN KOORDINASI MATA-TANGAN TERHADAP KEMAMPUAN PUKULAN LOB PADA MAHASISWA BULUTANGKIS UNTARA - Yudhi Esa Saputra; Siti Juabedah; Ghalih Kurniawan (JURNAL PENDIDIKAN DAN SAINS, 2022)
The problem of badminton athletes at the Universitas Tangerang Raya caused by the declining achievement factor experienced by athletes. The purpose of this study was to determine the contribution of arm muscle strength, waist flexibility, and hand-eye coordination to the lob ability of badminton athletes. The population of this study amounted to 59 people. The sampling technique was taken by "purposive sampling". The sample consisted of 30 male athletes aged 17-19 years. The data collected in this study were arm muscle strength with a push-up test, waist flexibility with a bridge-up test, eye-hand coordination with a tennis ball throwing and catching test, and lob hitting ability with a lob ability test. Data analysis techniques used descriptive statistical methods, then interpreted using a simple product moment for hypotheses one, two, three. The fourth hypothesis uses the dolitte double correlation formula. To determine the contribution of the independent variable to the dependent variable with the determination formula 1k xr1k x 100%. This research is included in the type of correlational research. The results of this study indicate: (1) There is an insignificant contribution between arm muscle strength and lob hitting ability, with a value of r = 0.130, r2 = 0.017, the contribution is 3.17%. (2) There is an insignificant contribution between waist flexibility and lob ability, with r = 0.082 obtained r2 = 0.007, the contribution is 0.79%. (3) There is no significant contribution between eye-hand coordination on lob hitting ability, with r = 0.247 obtained r2 = 0.061, the contribution is 8.04%. (4) There is an insignificant contribution between arm muscle strength, waist flexibility, and eye-hand coordination on lob hitting ability, with R = 0.436, R2 = 0.120, the contribution is 12%.